The Sensory Evaluation of Dairy Products - Clark, Stephanie; Drake, MaryAnne; Kaylegian, Kerry (Cham : Springer International Publishing : Imprint: Springer, 2023)
The Sensory Evaluation of Dairy Products, Third Edition is for all who seek a book entirely devoted to sensory evaluation of dairy products and modern applications of the science. It is an excellent scientific reference for training in dairy product evaluation and is a practical guide to the preparation of samples for sensory evaluation. The book contains updates of the original text of the well-received first edition, as well as brand new material. This unique book is designed for professionals involved in many aspects of dairy production, including academic teaching and research, processing, quality assurance, product development and marketing. It is an invaluable tool for those who compete in the annual Collegiate Dairy Product Evaluation Contest.
History of Sensory Analysis -- Psychological Considerations in Sensory Analysis -- Physiology of Sensory Perception -- Dairy Products Evaluation Competitions -- Fluid Milk and Cream Products -- Butter -- Creamed Cottage Cheese -- Yogurt -- Cheddar and Cheddar-Type Cheese -- Ice Cream and Related Products -- Concentrated and Dried Milk Products -- Pasteurized Process Cheese -- Sour Cream and Related Products -- Swiss Cheese and Related Products -- Mozzarella -- Latin American Cheeses -- Mold-ripened cheeses -- Goat and Sheep Cheeses -- Modern Sensory Practices.
Keywords: Food -- Microbiology; Food -- Sensory evaluation; Food science; Food Microbiology; Sensory Evaluation; Food Science